ANALISIS PRODUKTIVITAS SAPI BETINA INDUK DI SULAWESI TENGAH - Kaharuddin Kasim; Sagaf Sagaf; Abdul Basir Languha; Amiruddin Dg. Malewa (Universitas Tadulako, 2010)
The research conducted was aimed at investigating animal farming in Districts of Donggala, Parigi Moutong, and Banggai in Central Sulawesi. There were two subdistricts chosen as sampling sites from each disrict, and one village was chosen to represent each subdistrict. The villages were Malonas village (Damsol Subdistrict) and Sibedi village (Marawola Subdistrict) in Donggala, Parig Mpu village (Parigi Subdistrict) and Lambunu village (Tinombo Subdistrict) in Parigi Moutong, and Sinorang village (Batui Subdistrict) and Bualemo village (Bualemo Subbdistrict) in Banggai. The study sites were selected using a stratified sampling technique and was based on the highest cattle population number. Data were collected from field through a direct interview with respondents, which was aided with quetionnaries. The number of respondents (cattle keeper) interviewed was between 20 – 30% of the total population. The research results indicated that 78.56% of the respondents operated the cattle farms to increase the family income, but in the reality almost all farms was not feasible because of low cattle ownership and limited farmers’ skill in animal husbandry practices. On average, 87.98% of the respondents operated their cattle farms traditionally, 10.17% of them in category of semi intensive system while only 1.85% of them apply an intensive system. This led to a low technical coefficient for each individual variable of the cattle farms.